Maternal Vitamin D Level Is Associated with Viral Toll-Like Receptor Triggered IL-10 Response but Not the Risk of Infectious Diseases in Infancy - Sui-Ling Liao; Shen-Hao Lai; Ming-Han Tsai; Man-Chin Hua; Kuo-Wei Yeh; Kuan-Wen Su; Chi-Hsin Chiang; Shih-Yin Huang; Chuan-Chi Kao; Tsung-Chieh Yao; Jing-Long Huang (Hindawi Limited, 2016)
Reports on the effect of prenatal vitamin D status on fetal immune development and infectious diseases in childhood are limited. The aim of this study was to investigate the role of maternal and cord blood vitamin D level in TLR-related innate immunity and its effect on infectious outcome. Maternal and cord blood 25 (OH)D level were examined from 372 maternal-neonatal pairs and their correlation with TLR-triggered TNF-α, IL-6, and IL-10 response at birth was assessed. Clinical outcomes related to infection at 12 months of age were also evaluated. The result showed that 75% of the pregnant mothers and 75.8% of the neonates were vitamin deficient. There was a high correlation between maternal and cord 25(OH)D levels (r=0.67, p<0.001). Maternal vitamin D level was inversely correlated with IL-10 response to TLR3 (p=0.004) and TLR7-8 stimulation (p=0.006). However, none of the TLR-triggered cytokine productions were associated with cord 25(OH)D concentration. There was no relationship between maternal and cord blood vitamin D status with infectious diseases during infancy. In conclusion, our study had shown that maternal vitamin D, but not cord vitamin D level, was associated with viral TLR-triggered IL-10 response.